Evaluation of bacterial safety approaches of platelet blood concentrates: bacterial screening and pathogen reduction - Rezvany, Mohammad Reza; Moradi Hasan-Abad, Amin; Sobhani-Nasab, Ali; Esmaili, Mohammad Ali (Frontiers in Medicine, 2024)
This mini-review analyzed two approaches to screening bacterial contamination and utilizing pathogen reduction technology (PRT) for Platelet concentrates (PCs). While the culture-based method is still considered the gold standard for detecting bacterial contamination in PCs, efforts in the past two decades to minimize transfusion-transmitted bacterial infections (TTBIs) have been insufficient to eliminate this infectious threat. PRTs have emerged as a crucial tool to enhance safety and mitigate these risks. The evidence suggests that the screening strategy for bacterial contamination is more successful in ensuring PC quality, decreasing the necessity for frequent transfusions, and improving resistance to platelet transfusion. Alternatively, the PRT approach is superior regarding PC safety. However, both methods are equally effective in managing bleeding. In conclusion, PRT can become a more prevalent means of safety for PCs compared to culture-based approaches and will soon comprehensively surpass culture-based bacterial contamination detection methods.